Research progress on correlation of furosemide with contrast-induced nephropathy - LIN Kai-yang; CHEN Han-chuan; WANG Sun-ying; GUO Yan-song (Linchuang shenzangbing zazhi)
With rapid development of radiology and intervention diagnosis and treatment, use of contrasts is becoming more and more common. Contrast-induced nephropathy(CIN) has become one of the most common complications which increases the risk for mortality of dialysis, prolongs hospitalization, and raises medical cost, so as to influence life quality and health of patients greatly. However, there is no effective treatment approach for CIN. Only hydration has so far been the most evidence-based and the most effective way among CIN preventive strategies, and has been widely used in clinical practice. However, in patients at high risk for CIN with chronic kidney disease and congestive heart failure,inappropriate hydration may aggravate the damage of heart and kidney functions. Therefore, how to achieve "sufficiency" and avoid "excessiveness" is crucial. Furosemide is a widely used drug in patients with heart and kidney insufficiency, whether it increase or decrease the risk for CIN is unknown. This article is purposed to provide a brief outline of CIN and a review of research progress on correlation of furosemide with CIN.